Comparing Two Different Concentrations of Diphenhydramine Versus Lidocaine for Median Nerve Block in Emergency Department: A Double-Blind Randomized Clinical Trial - Shervin Farahmand; Fariba Yazdanbakhsh; Shahram Bagheri-Hariri; Ehsan Aliniagerdroudbari; Atefeh Abdollahi; Sepideh Babaniamansour (Eurasian Journal of Emergency Medicine, 2021)

(untitled)
Aim:This study aimed to compare two different concentrations of Diphenhydramine vs. Lidocaine for median nerve block in terms of providing required anesthesia for repairing soft tissue injuries.Materials and Methods:This double-blind, randomized clinical trial was conducted in Tehran, Iran, in 2019. Participants were randomly assigned to three groups. Group A received 3 cc of 0.5% diphenhydramine (n=68), group B received 3 cc of 1% lidocaine (n=68), and group C received 3 cc of 1% diphenhydramine (n=68). The onset of action, duration of anesthesia, pain during injection, and patients’ satisfaction level were evaluated between the groups.Results:Two hundred two patients with the mean age of 35.09±13.5 years took part in this study (52.5% of the males). Age (p=0.879), onset of action (p=0.251) and duration of anesthesia (p=0.081) had no significant difference among the three groups. The pain during injection between groups A and B (p=0.001) and between groups B and C (p<0.0001) had significant differences. Patients in group B had the significant highest level of satisfaction (p<0.0001).Conclusion:In our study, two different concentrations of diphenhydramine had the same onset of action and duration of anesthesia compared to lidocaine. Lidocaine caused lower pain during injection compared to diphenhydramine, and the level of satisfaction was higher with lidocaine. Diphenhydramine had no significant difference with different concentrations in terms of pain during injection.